Genetic progress achieved in bean breeding in Uganda - Mukayiranga, A.; Rubaihayo, P.; Edema , R.; Nkalubo, S.T.; Rutayisire, A. (African Crop Science Journal, 2022)
Several cultivars of common bean (Phaseolus vulgaris L.) have been released in Uganda over a period of five decades, but the genetic gain to selection in respect of yield and agronomic characteristics has not been determined. This study was conducted to estimate the gain in selection over the 1960 - 2016 period, of common bean breeding in Uganda. Twenty nine bush and eleven climbing type cultivars were evaluated for yield and yield components, in three locations, during 2017B and 2018A cropping seasons. The study was carried out at the National Crop Resources Research Institute (NaCCRI), Nakabango Research Institute in central and Kwachwekano Zonal Agriculture Research Institute in southwestern Uganda. The design used was a randomised complete blocks with three replicates for the climbing types; and a 3x10 Alpha lattice design with three replicates for bush types. Significant differences (P<0.001) were recorded among cultivars for most traits in both bush and climbers, except seed number per pod (NSP). The range of genetic gain in grain yield was between 1,505 to 2,418 kg ha-1 for bush type cultivars, and 1,641 to 2,687 kg ha-1 for the climbing types. Yield has increased by16.3 and 26.3 kg ha-1 per year for bush and climbers, respectively; with a relative gain of 1.27%/year for bush types and 1.54%/year for the climbing types. Biomass yield and harvest index explained most of the variation in grain yield and number of pods per plant in climbing types. Among climbing types, biomass yield was significantly and positively correlated with grain yield per plant and grain yield per ha (P<0.05, and r= 0.87) and with grain yield per ha (P<0.01 r = 0.98) for bush types, biomass yield was significantly and positively correlated with grain yield per plant (P<0.05, and r= 0.59) and with grain yield per ha (P<0.01 r = 0.80) and harvest index (P<0.5 r = 0.80).